Altered mRNAs Profiles in the Testis of Patients With “Secondary Idiopathic Non-Obstructive Azoospermia” - Tang, Dongdong; Li, Kuokuo; Lv, Mingrong; Xu, Chuan; Geng, Hao; Wang, Chao; Cheng, Huiru; He, Xiaojin; Zhang, Yan; Cao, Yunxia (Frontiers in Cell and Developmental Biology, 2022)
Background: Non-obstructive azoospermia (NOA) is the most severe form of male infertility. Currently known causative factors, including congenital and several acquired causes can only account for approximately 30% of NOA cases. Causes for most patients with NOA remains unclear, which were known as idiopathic NOA (iNOA). However, whether iNOA is congenital defects or acquired abnormalities is a confusing problem due to the delayed diagnosis of this frustrating situation until childbearing age. Materials and Methods: In this study, several patients who were diagnosed as iNOA at this stage, but with a history of natural conceptions with female before were enrolled and defined as “secondary idiopathic NOA”. As little was known about these cases, we performed the mRNA expression profiling by Next-generation sequencing (NGS) in this three patients and other three patients with obstructive azoospermia (OA) as controls. Results: A series of mRNAs were found to be altered in testicular tissues between “secondary idiopathic NOA” and controls, including 6028 downregulated and 3402 upregulated mRNAs. GO analysis and KEGG analysis revealed a range of GO and KEGG terms, such as cellular process involved in reproduction, protein digestion and absorption, etc. Conclusion: Overall, this study introduces a novel classification called “secondary idiopathic NOA” in iNOA. We provide a global view of the altered mRNAs involved in spermatogenetic failure in these cases.